Plenty of accurate novel solitary wave solutions of the fractional Chaffee–Infante equation - Khater, Mostafa M.A.; Alfalqi, Suleman H.; Alzaidi, Jameel F.; Attia, Raghda A.M. (Results in physics, 2023)
This work focuses on the accuracy and numerical strategies for solving the fractional Chaffee–Infante (CIE) equation in (2+1) dimensions computationally. This model illustrates the flow and transformation of gas as it travels through a homogeneous medium. When the constituents of a medium do not alter from their initial state, we say that the medium is homogeneous. In none of the solutions did we change the proportions of the individual components. Three novel analytical and numerical techniques provide new, dependable approaches for determining and estimating responses. The tabular data shown here facilitates interpreting the numerical data presented below. The simulations, which are exhibited in both 2D and 3D, depict the behavior of a solitary solitaire in both the natural and digital worlds. These findings demonstrate that this strategy is the most effective way to solve nonlinear mathematical physics problems. •Study the computational solutions of Fractal Chaffee–Infante equation.•Computational and Numerical simulations.•Analytical and numerical novel constructed results.•Investigating the obtained results’ accuracy.•Explaining the obtained solutions through some distinct types of sketches.